Предмет: Математика,
автор: тоха12345678902004
Разложите на множители !!!!
Приложения:
Ответы
Автор ответа:
0
Ну как-то так, могу переписать если не видно
Приложения:
Автор ответа:
0
=4(х+1)-а(х+1)=(4-а)(х+1)
=2а(3х-1)+5(3х-1)=(2а+5)(3х-1)
=9х(х-у)-5(х-у)=(9х-5)(х-у)
=3х(2х-1)-у(2х-1)=(3х-у)(2х-1)
--------------------------------
=(6х-11у)(6х+11у)
=(9х-4у)(9х+4у)
=(2ху-1/3z²)(2ху+1/3z²)
=(3х²-1/4уz³)(3х²+1/4уz³)
=(2х⁴-1/5у⁶)(2х⁴+1/5у⁶)
=(х-2)(х²+2х+4)
=(х+3)(х²-3х+9)
=2а(3х-1)+5(3х-1)=(2а+5)(3х-1)
=9х(х-у)-5(х-у)=(9х-5)(х-у)
=3х(2х-1)-у(2х-1)=(3х-у)(2х-1)
--------------------------------
=(6х-11у)(6х+11у)
=(9х-4у)(9х+4у)
=(2ху-1/3z²)(2ху+1/3z²)
=(3х²-1/4уz³)(3х²+1/4уz³)
=(2х⁴-1/5у⁶)(2х⁴+1/5у⁶)
=(х-2)(х²+2х+4)
=(х+3)(х²-3х+9)
Похожие вопросы
Предмет: Математика,
автор: farid010709
Предмет: Музыка,
автор: lizok8788
Предмет: История,
автор: Akira01022
Предмет: Математика,
автор: 22252
Предмет: Литература,
автор: Wesgluf